Antidepressant Prescribing and Suicide/Self-Harm by Young Australians: Regulatory Warnings, Contradictory Advice, and Long-Term Trends - Whitely, Martin; Raven, Melissa; Jureidini, Jon (Frontiers in Psychiatry, 2020)
In 2004, the US Food and Drug Administration (FDA) controversially warned that antidepressants were associated with an increased risk of suicidal thoughts and behaviours in people aged under 25 years. Subsequently there was considerable debate, and at times emotive backlash, in academic journals and the international media. In 2005, the Australian Therapeutic Goods Administration responded to the FDA warning by requiring Product and Consumer Information leaflets to be updated to reflect the risk. However, prominent Australian mental health organisations and psychiatrists challenged the FDA warning. They argued that, on balance, antidepressant use was likely to reduce the risk of suicide. To support this, an Australian ecological study was repeatedly cited misleadingly as evidence of an inverse causal relationship, a tactic also used in the US. From 2008 to 2018, Australian per-capita child, adolescent and young adult antidepressant prescribing (0-27 years of age) and suicide (0-24 years) rates have increased approximately 66% and 49% respectively. In addition, there was a 98% increase in intentional poisonings among 5 to 19 year-olds in New South Wales and Victoria between 2006 and 2016, with substantial overlap between the most commonly dispensed psychotropics and the drugs most commonly used in self-poisoning. Far from supporting expert claims that increased antidepressant use would reduce youth suicide rates, these results are more consistent with the hypothesis that antidepressants increase suicidality and self-harm in young people. Furthermore, there is compelling evidence that the antidepressants prescribed to young Australians are frequently the means of self-harm. Similar dynamics have occurred in several other countries. Regulatory warnings have been strategically challenged, and have had little impact on escalating prescribing rates, accompanied by increasing rates of suicide and self-harm.